Retrospective comparative study of IV+ local tranexamic acid versus IV tranexamic acid only in primary total knee replacement - Kamat, Sanil G.; Dessai, Rohan (International Journal of Research in Orthopaedics, 2021)
Background: The study is to compare the immediate post-operative outcomes with use of intravenous (IV) tranexamic acid (TXA) versus IV and local TXA combination in primary unilateral total knee arthroplasty. Study comprised of 72 cases of tricompartmental knee primary osteoarthritis who have undergone unilateral total knee arthroplasty at Manipal Hospital, Goa from January 2016 to December 2018. The observations for each group was analysed and post op blood loss in drain, fall of haemoglobin levels and need of blood transfusion was recorded. The results were statistically compared. The mean blood loss fall in HB levels and need of blood transfusions revealed statistically significant differences. Methods: Total 72 patients diagnosed with primary tricompartmental osteoarthritis were divided into two groups retrospectively. Group 1 (IV only): 1 gm IV Tranexamic acid bolus 10 min before deflating the tourniquet. Group 2 (IV + Local): 1 gm IV Tranexamic acid bolus 10 min before deflating the tourniquet and 1 gm Tranexamic Acid in 50 ml saline locally at the time of closure. Results: It was observed that higher post op blood loss, higher fall in haemoglobin (HB) levels and higher requirement of blood transfusions were associated with group 1 as compared to 2. Conclusions: The study inferred that the combination of local and systemic tranexamic acid was superior than systemic administration alone with lower post op blood loss, lower rates of blood transfusion and lower fall in haemoglobin levels without any added complications.